Health-Related Quality of Life After Complete Versus Infarct Artery-only Percutaneous Coronary Revascularization in Multi-Vessel Disease with St Segment Elevation Myocardial Infarction - Muhammad Rehanul Haq, Javed Khurshed Shaikh, Muhammad Hashim Kalwar, Muhammad Hassan Butt, Altaf Hussain Gajoo, Syed Nadeem Hassan Rizvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study was to compare the HRQoL of patients who had complete revascularization at the time of the first admission to those who underwent revascularization of the infarct artery alone using the EQ-5D (European quality of life-5 dimensions) self-report questionnaire. Background: The effect of revascularization procedures on health-related quality of life (HRQoL) in patients with multivessel disease who undergo primary percutaneous coronary intervention is the subject of controversy (P-PCI). Methods and Results: There was a significant difference between individuals with STEMI who received revascularization of the infarct-related artery alone and those who got total revascularization. we divided the group by the extent of complete revascularization (n=147) or the extent of IRA-only revascularization (n = 153) during the index admission Mobility, self-care, routine activity, pain or discomfort, anxiety, and sadness were all evaluated using the EQ-5D scale. The prevalence of heart failure and the gender of patients were different at baseline. Patients who had full revascularizations had lower mean ±SD (EQ-VAS and EQ-5D) utility ratings than those who had infarct artery revascularizations alone after 2 years of follow-up. (70.00 (±19.9) vs. 51.04 (±17.8), P < 0.04, and 0.71 (±0.03) vs0.61 (±0.03), P<0.005, respectively). Conclusion: Complete revascularization produced clinically significant increases in quality of life when compared to treating just the IRA at 24 months.